Evaluation of dosimetric advantages of using patient‐specific aperture system with intensity‐modulated proton therapy for the shallow depth tumor. (27th November 2017) - Yasui, Keisuke; Toshito, Toshiyuki; Omachi, Chihiro; Hayashi, Kensuke; Tanaka, Kenichiro; Asai, Kumiko; Shimomura, Akira; Muramatsu, Rie; Hayashi, Naoki
Abstract: In this study, we evaluate dosimetric advantages of using patient‐specific aperture system with intensity‐modulated proton therapy (IMPT) for head and neck tumors at the shallow depth. We used four types of patient‐specific aperture system (PSAS) to irradiate shallow regions less than 4 g/cm 2 with a sharp lateral penumbra. Ten head and neck IMPT plans with or without aperture were optimized separately with the same 95% prescription dose and same dose constraint for organs at risk (OARs). The plans were compared using dose volume histograms (DVHs), dose distributions, and some dose indexes such as volume receiving 50% of the prescribed dose (V50 ), mean or maximum dose (Dmean and Dmax ) to the OARs. All examples verified in this study had decreased V50 and OAR doses. Average, maximum, and minimum relative reductions of V50 were 15.4%, 38.9%, and 1.0%, respectively. Dmax and Dmean of OARs were decreased by 0.3% to 25.7% and by 1.0% to 46.3%, respectively. The plans with the aperture over more than half of the field showed decreased V50 or OAR dose by more than 10%. The dosimetric advantage of patient‐specific apertures with IMPT was clarified in many cases. The PSAS has some dosimetric advantages for clinical use, and in some cases, it enables to fulfill dose constraints.